PENTINGNYA PEMBELAJARAN DALAM MENGEMBANGKAN KEMAMPUAN BAHASA PADA ANAK SEKOLAH DASAR - Nasra, Nasra (Jurnal Sultra Elementary School, 2023)
Language skills are one of the important aspects in the development of elementary school children. Effective language learning can help children develop communication skills, critical thinking, and literacy skills that are the basis for academic success. This article aims to review various literature related to the importance of language learning in the context of elementary school education. This literature study approach identifies methods, strategies, and challenges in language learning and their impact on children's cognitive and social development. The results of the study indicate that language learning integrated with an experiential and technology-based approach provides significant results in improving children's language skills.